2003
DOI: 10.1039/b308948g
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of addition–elimination reactions in pyrimidines and purines using trifluoroacetic acid in trifluoroethanol

Abstract: SNAr displacement reactions of 6-cyclohexylmethoxy-2-fluoropurine, 6-amino-2-butylsulfonyl-4-cyclohexylmethoxypyrimidine and 2-amino-6-chloropurine with substituted anilines (e.g. the weakly nucleophilic 4-aminobenzenesulfonamide) are dramaticallyaccelerated in the presence of trifluoroacetic acid and occur especially efficiently in 2,2,2-trifluoroethanol solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 11 publications
(6 reference statements)
1
39
0
Order By: Relevance
“…[2,8,29] In earlier studies we focused on the use of TFA-TFE with conventional heating. [7] We have now found that the more difficult substitutions can be facilitated by microwave heating. [15,30] Furthermore, it is sometimes convenient to use an aniline hydrochloride as reactant, with the hydrogen chloride liberated providing acidic catalysis.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…[2,8,29] In earlier studies we focused on the use of TFA-TFE with conventional heating. [7] We have now found that the more difficult substitutions can be facilitated by microwave heating. [15,30] Furthermore, it is sometimes convenient to use an aniline hydrochloride as reactant, with the hydrogen chloride liberated providing acidic catalysis.…”
Section: Discussionmentioning
confidence: 89%
“…The syntheses of heterocyclic substrates used in this study, when not commercially available, have either been described [5,[7][8][9] or utilised standard methods (see the Experimental Section and the Supporting Information). Table 1 and Table 2 summarise the panel of heterocycles and anilines that have been examined (further examples are given in the Supporting Information, Table S1).…”
Section: Synthesis Of Substratesmentioning
confidence: 99%
See 2 more Smart Citations
“…This is supported by the observation that reactions of 2-fluoroimidazole, a model analog of 8-fluoropurines with nucleophiles, follow an addition-elimination mechanism [20]. Interestingly, reactions of certain substituted chloropurines have also been reasoned to occur via S N Ar mechanisms [21]. Thus, in the S N Ar reaction shown in Scheme 4 the addition of NH 3 to the 8-fluoropurines 2, a likely ratedetermining step [22], would lead to the formation of the Meisenheimer complex [23] 15 which could collapse to the corresponding 8-amino derivatives 8.…”
Section: Defluorination Studiesmentioning
confidence: 86%